Goals of Care Conversation to Support Patient Empowerment in Managing Cancer Care - Martinez, Gary (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
“Goals of care” (GoC) refers to a patient’s values, goals, and treatment preferences in severe illness. GoC conversations are crucial to the care of cancer patients and involve patient and family decision-making and autonomy. A case study of a man experiencing HPV-related throat cancer illustrates how emotional factors and potential loss of independence may create a GoC conflict of values. In this case, the ethicist’s role is to mediate and protect the patient-provider trust relationship. When acted upon early in the cancer care trajectory, such ethics-based communication may promote patient-family commitment and clinical progress and improve quality of life.